Ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and preparation method thereof

By using nanopowders, fly ash microbeads, modified polycarboxylic acid water reducers and highly absorbent resins in ultra-high performance concrete, the problems of high viscosity, low early strength and shrinkage are solved, and better construction performance and durability are achieved.

CN118954998BActive Publication Date: 2025-04-29CHANGCHUN URBAN CONSTR & MAINTENANCE GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411012163.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-04-29
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

Ultra-high performance concrete has high viscosity problems, which leads to difficulty in pouring concrete and degradation of crack resistance. At the same time, it has low strength in the early stage and is prone to shrinkage.

Method used

Admixtures composed of nanopowder, fly ash microbeads, modified polycarboxylic acid water reducer, gas induction agent and highly absorbent resin are used to regulate the component ratio to reduce concrete viscosity, improve early strength and inhibit shrinkage.

Benefits of technology

It effectively reduces the viscosity of concrete, improves early strength, prevents concrete from shrinking, and improves construction performance and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004964702130000081
    Figure BDA0004964702130000081
  • Figure BDA0004964702130000082
    Figure BDA0004964702130000082
Patent Text Reader

Abstract

The present invention belongs to the field of building materials, and particularly relates to an ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof, comprising the following components by weight: 5-10 parts of nano powder, 20-35 parts of fly ash microspheres, 15-25 parts of modified polycarboxylic acid water reducer, 1-3 parts of air entraining agent and 5-15 parts of highly absorbent resin. The concrete admixture prepared by the present invention can reduce the viscosity of concrete, improve the early strength of concrete and inhibit the shrinkage of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and particularly relates to an ultra-high performance concrete admixture capable of reducing viscosity and inhibiting shrinkage, and a preparation method thereof. Technical Background

[0002] Ultra-high performance concrete is an important innovation in the field of building materials in recent years. With its excellent performance and unique physical properties, this concrete is gradually changing the traditional fields of construction and civil engineering. The development background of ultra-high performance concrete stems from the demand for concrete materials with higher strength, longer life and better durability, especially for engineering structures used in extreme environments and heavy load conditions. The uniqueness of ultra-high performance concrete lies in its extremely high compressive and tensile strengths, which is mainly due to its special composition and preparation process. It uses optimized particle grading, combined with micron and submicron cement-based materials, as well as high-efficiency water reducers and fiber reinforcements. This combination gives ultra-high performance concrete excellent mechanical properties, such as ultra-high compressive strength and excellent durability, including anti-penetration, anti-freeze and thaw, and anti-chemical erosion.

[0003] However, ultra-high performance concrete still has the problem of high viscosity, which makes it difficult to pour concrete and even causes exhaust difficulties, resulting in reduced crack resistance of concrete. For example, CN116102691B discloses "viscosity reducing and water-reducing agent for high-strength concrete and preparation method thereof", which is prepared with unsaturated acid, initiator, chain transfer agent, polyether macromonomer and ester hydrophobic monomer as main components, can improve the fluidity of concrete and reduce viscosity for a long time. However, studies have shown that while the fluidity of concrete is enhanced, the early strength will be weakened. The patent does not mention and solve the problem of low early strength of concrete.

[0004] For example, CN114349384B discloses a "viscosity-reducing water-reducing agent" which is prepared by synthesizing a modified acrylic acid solution with acrylic acid and 2-methylallyl polyoxyethylene ether as main raw materials, and then copolymerizing with various functional monomers and adding silicon carbide nanowhiskers. It has good viscosity-reducing and alkaline water effects and improves the compressive strength of concrete. However, the patent does not mention and solve the problem of how to prevent concrete shrinkage.

[0005] Therefore, it is urgent to develop an admixture that can reduce the viscosity of concrete, improve the early strength of concrete and inhibit the shrinkage of concrete. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides an ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof. The admixture can reduce the viscosity of concrete, while improving the early strength of concrete and inhibiting concrete shrinkage.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides an ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage, comprising the following components by weight: 5 to 10 parts of nano powder, 20 to 35 parts of fly ash microspheres, 15 to 25 parts of modified polycarboxylic acid water reducer, 1 to 3 parts of air entraining agent and 5 to 15 parts of super absorbent resin.

[0009] In some embodiments, the nano powder is nano SiO2 and / or nano Al2O3.

[0010] In some embodiments, the preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:

[0011] (1) 3-butenoic acid, cis-1,2-dihydroxymethylethylene and a solvent are mixed, concentrated sulfuric acid is added, the temperature is raised to 60-70° C. and stirred for 8-10 hours, deionized water is added for extraction, the organic phase is collected, and the organic phase is concentrated under reduced pressure and subjected to column chromatography to obtain compound A;

[0012] (2) Mix propyltrimethoxysilane, methanol and deionized water, heat to 80-100° C. and stir at constant temperature for 1-1.5 hours, then add compound A and dilute nitric acid in step (1) and heat to 100-110° C. and stir at constant temperature for 8-12 hours to obtain compound B;

[0013] (3) adding acrylic acid, compound B in step (2) and methacrylic acid polyethylene glycol ether to water and stirring at a constant temperature of 25 to 35° C. for 30 to 40 minutes, then adding an initiator, an oxidant and a reducing agent, heating to 65 to 75° C. and stirring at a constant temperature for 2 to 3 hours, cooling to room temperature after the reaction is completed, and adjusting the pH of the system to 5 to 8 with a sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water-reducing agent precursor;

[0014] (4) Add fumed silica and hydroxypropyl methylcellulose to the modified polycarboxylic acid water-reducing agent precursor in step (3), raise the temperature to 40-60° C., and stir at a constant temperature for 8-10 hours to obtain a modified polycarboxylic acid water-reducing agent.

[0015] The applicant found that when preparing ultra-high performance concrete, its viscosity is too large, which is not conducive to construction and pouring, and during the molding process, the compressive strength of the concrete can not be discharged in time, and the common method is to add a water reducer, which can not only reduce the amount of water but also improve the dispersion effect of the concrete, but the early strength of the concrete has decreased. The concrete admixture of the present application can not only improve the dispersion performance of the concrete but also prevent the problem of the early compressive strength of the concrete from decreasing. The reason may be that the polycarboxylic acid chain segment in the modified polycarboxylic acid water reducer can adsorb on the concrete surface, and the silanol structure therein reacts with the fumed silica to form siloxane so that the fumed silica can be inserted between the molecular segments of the modified polycarboxylic acid water reducer, and the ester group can greatly improve the dispersibility between the concrete particles and improve the flowability of the concrete. In addition, the applicant adds hydroxypropyl methylcellulose, which can react with the silanol through hydrogen bonds to form a micro-cross-linked network structure to prevent the early strength of the concrete from decreasing.

[0016] In some embodiments, in step (1), the molar ratio of 3-butenoic acid to cis-1,2-dihydroxymethylethylene is 1:(0.9-1).

[0017] The present application can make the esterification reaction more complete by regulating the molar ratio of 3-butenoic acid and cis-1,2-dihydroxymethylethylene, thereby saving raw materials and thus costs.

[0018] In some embodiments, the solvent is methanol and / or ethanol.

[0019] In some embodiments, in step (2), the molar ratio of propyltrimethoxysilane to compound A is 1:(1-1.2).

[0020] In some embodiments, in step (3), the mass ratio of acrylic acid, compound B and methacrylate polyethylene glycol ether is 1:1:(1.2-2.2).

[0021] In some embodiments, in step (4), the mass ratio of the modified polycarboxylate water-reducing agent precursor, fumed silica and hydroxypropyl methylcellulose is 1:(1-1.2):(0.4-0.8).

[0022] The present application can prevent the early strength or flowability of concrete from decreasing by regulating the mass ratio of the modified polycarboxylate water-reducing agent precursor, fumed silica and hydroxypropyl methylcellulose.

[0023] In some embodiments, the air entraining agent is an alkylbenzene sulfonate.

[0024] In some embodiments, the method for preparing the super absorbent resin comprises the following steps:

[0025] (I) maleic acid and thionyl chloride are mixed, the temperature is raised to 60-80°C and stirred for 0.5-1h, after the reaction is completed, the temperature is restored to room temperature, and the mixture is concentrated under reduced pressure to obtain compound C;

[0026] (II) Compound C in step (I) is mixed with tetrahydrofuran, an acid binding agent is added thereto, and a chloroform solution of 1,2-propylenediamine is added dropwise at a rate of 5 to 10 mL / min. After the addition is complete, the mixture is stirred at room temperature for 2 to 4 hours. After the reaction is completed, the mixture is filtered, concentrated under reduced pressure, and subjected to column chromatography to obtain compound D;

[0027] (III) N,N-methylenebisacrylamide, the compound D in step (II) and the initiator are dissolved in water, the temperature is raised to 65-75° C. and stirred at the constant temperature for 20-24 hours. After the reaction is completed, spray drying is performed to obtain a highly absorbent resin.

[0028] The applicant found in the research that concrete admixtures can improve the fluidity, dispersibility and early strength of concrete, but during the shaping stage, shrinkage occurs due to the evaporation and drying of water. The applicant has made a highly absorbent resin that can absorb a large amount of water when mixing. When the water evaporates after the concrete is formed, the highly absorbent resin can provide moisture and reduce the shrinkage of the concrete. In addition, the applicant found that common highly absorbent resins have weak alkali resistance, while the highly absorbent resin of the present application uses amide groups as the main hydrophilic groups, which can make the highly absorbent resin more suitable for concrete environments, improve the curing effect inside the concrete, and extend the action time of the concrete admixture.

[0029] In some embodiments, in step (I), the molar ratio of maleic acid to thionyl chloride is 1:(2-2.2).

[0030] In some embodiments, in step (II), the molar ratio of compound A to 1,2-propylenediamine is 1:(0.8-1).

[0031] In some embodiments, in step (III), the mass of the N,N-methylenebisacrylamide is 0.07-0.09 wt % of compound D.

[0032] The present application can prevent the deterioration of the anti-shrinkage performance of concrete due to the poor water absorption performance caused by the overly dense cross-linked network structure by regulating the mass ratio of N,N-methylenebisacrylamide and compound B.

[0033] On the other hand, the present invention provides a method for preparing an ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage, comprising the following steps: mixing nano powder, fly ash microbeads, air entraining agent and super absorbent resin and packaging them separately as solid components, packaging modified polycarboxylic acid water reducer separately as liquid components, and mixing the solid components and the liquid components to obtain the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The ultra-high performance concrete admixture of the present invention is prepared by nano powder, fly ash microspheres, modified polycarboxylic acid water reducer, air entraining agent and super absorbent resin, which can reduce the viscosity of concrete, improve the early strength of concrete and inhibit the shrinkage of concrete.

[0036] (2) The present invention utilizes nano-SiO2, nano-Al2O3 and fly ash microspheres to optimize the particle composition of the cementitious material. The compounded polycarboxylic acid water-reducing agent can not only reduce the viscosity of the concrete and improve the construction performance, but also increase the density of the slurry, thereby improving the strength and durability of the ultra-high performance concrete.

[0037] (3) The modified polycarboxylic acid water-reducing agent of the present invention can not only improve the dispersion performance of concrete but also prevent the problem of decrease in the initial compressive strength of concrete.

[0038] (4) The highly water-absorbent resin of the present invention has the function of strong water absorption and slow water release through penetration. After the concrete is formed, it will slowly release the internal moisture over time, so that the concrete can be fully internally cured and the autogenous shrinkage and drying shrinkage of the concrete can be greatly reduced. In addition, the highly water-absorbent resin of the present invention can fully play its role in the alkaline environment of concrete, thereby extending the action time of the concrete admixture. DETAILED DESCRIPTION

[0039] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0040] In the following preparation examples, embodiments and comparative examples, fly ash microbeads were purchased from Chengdu Kelian Building Materials Co., Ltd.; polyethylene glycol methacrylate was purchased from Wuhan Kemik Biomedicine Technology Co., Ltd.; nano-SiO2 was purchased from Dachun (Hebei) Building Materials Technology Co., Ltd.; triterpenoid saponins were purchased from Nanjing Xinyi Synthesis Technology Co., Ltd.; and polycarboxylic acid water reducer was purchased from Jinan Boci Trading Co., Ltd.

[0041] Preparation Example 1

[0042] The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:

[0043] (1) 10 g of 3-butenoic acid, 10.2 g of cis-1,2-dihydroxymethylethylene and 100 mL of anhydrous methanol were mixed, 0.3 g of 98 wt% concentrated sulfuric acid was added, the temperature was raised to 65° C. and the mixture was stirred for 9 h, deionized water was added to extract and the organic phase was collected, and the mixture was concentrated under reduced pressure and subjected to column chromatography to obtain compound A;

[0044] (2) 17 g of propyltrimethoxysilane, 20 g of methanol and 60 g of deionized water were mixed and heated to 90° C. and stirred at this temperature for 1.3 h, and then 18 g of the compound A in step (1) and 3 g of 40 wt % dilute nitric acid were added and heated to 105° C. and stirred at this temperature for 10 h to obtain compound B;

[0045] (3) adding 10 g of acrylic acid, 10 g of the compound B in step (2) and 18 g of methacrylate polyethylene glycol ether to water and stirring at a constant temperature of 30 ° C for 35 min, then adding 3 g of dimethyl azobisisobutyrate, 4 g of hydrogen peroxide and 8.6 g of ascorbic acid, heating to 70 ° C and stirring at a constant temperature for 2.5 h, cooling to 27 ° C after the reaction is completed, and adjusting the pH of the system to 5 with a 32 wt % sodium hydroxide aqueous solution to obtain a modified polycarboxylate water-reducing agent precursor;

[0046] (4) Add 33 g of fumed silica and 18 g of hydroxypropyl methylcellulose to 30 g of the modified polycarboxylic acid water-reducing agent precursor in step (3), raise the temperature to 50° C. and stir at a constant temperature for 9 h to obtain a modified polycarboxylic acid water-reducing agent.

[0047] Preparation Example 2

[0048] The preparation method of the modified polycarboxylic acid water-reducing agent is the same as that of Preparation Example 1, except that the mass of 3-butenoic acid is 16 g.

[0049] Preparation Example 3

[0050] The preparation method of the modified polycarboxylic acid water-reducing agent is the same as that of Preparation Example 1, except that the mass of propyltrimethoxysilane is 25 g.

[0051] Preparation Example 4

[0052] The preparation method of the modified polycarboxylic acid water-reducing agent is the same as that of Preparation Example 1, except that the mass of the fumed silica is 43 g.

[0053] Preparation Example 4

[0054] The preparation method of the super absorbent resin comprises the following steps:

[0055] (I) 10 g of maleic acid and 20.5 g of thionyl chloride were mixed, the temperature was raised to 70° C. and stirred for 0.7 h. After the reaction was completed, the temperature was restored to 27° C. and the mixture was concentrated under reduced pressure to obtain compound C;

[0056] (II) 13 g of the compound C prepared in step (I) was mixed with 150 mL of tetrahydrofuran, 0.1 g of sodium bicarbonate was added thereto, and 10 mL of a chloroform solution containing 0.07 g of 1,2-propylenediamine was added dropwise at a rate of 7 mL / min. After the addition was complete, the mixture was stirred at room temperature for 3 h. After the reaction was completed, the mixture was filtered, concentrated under reduced pressure, and subjected to column chromatography to obtain compound D;

[0057] (III) 0.015 g of N,N-methylenebisacrylamide, 19 g of the compound D prepared in step (II) and 0.02 g of sodium persulfate were dissolved in 200 mL of water, the temperature was raised to 70° C. and stirred at this temperature for 22 h. After the reaction was completed, the mixture was spray-dried to obtain a highly absorbent resin.

[0058] Preparation Example 5

[0059] The preparation method of the highly absorbent resin is the same as that of Preparation Example 4, except that the mass of N,N-methylenebisacrylamide is 0.5 g.

[0060] Example 1

[0061] A ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage comprises the following components by weight: 7 parts of nano-SiO2, 25 parts of fly ash microspheres, 20 parts of modified polycarboxylic acid water reducer, 2 parts of triterpenoid saponin and 10 parts of highly absorbent resin.

[0062] Among them, the modified polycarboxylic acid water-reducing agent is prepared by Preparation Example 1, and the super absorbent resin is prepared by Preparation Example 4.

[0063] The preparation method of the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage in this embodiment comprises the following steps: nano-SiO2, fly ash microbeads, triterpenoid saponin and super absorbent resin are mixed and packaged separately as solid components, and modified polycarboxylic acid water reducer is packaged separately as liquid components. The solid components and liquid components are mixed when used to obtain the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage.

[0064] Example 2

[0065] A ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage comprises the following components by weight: 5 parts of nano-SiO2, 20 parts of fly ash microspheres, 15 parts of modified polycarboxylic acid water reducer, 1 part of triterpenoid saponin and 5 parts of highly absorbent resin.

[0066] Among them, the modified polycarboxylic acid water-reducing agent is prepared by Preparation Example 1, and the super absorbent resin is prepared by Preparation Example 4.

[0067] The preparation method of the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage in this embodiment comprises the following steps: nano-SiO2, fly ash microbeads, triterpenoid saponin and super absorbent resin are mixed and packaged separately as solid components, and modified polycarboxylic acid water reducer is packaged separately as liquid components. The solid components and liquid components are mixed when used to obtain the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage.

[0068] Example 3

[0069] A ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage comprises the following components in parts by weight: 10 parts of nano-SiO2, 35 parts of fly ash microbeads, 25 parts of modified polycarboxylic acid water reducer, 3 parts of triterpenoid saponin and 15 parts of highly absorbent resin.

[0070] Among them, the modified polycarboxylic acid water-reducing agent is prepared by Preparation Example 1, and the super absorbent resin is prepared by Preparation Example 4.

[0071] The preparation method of the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage in this embodiment comprises the following steps: nano-SiO2, fly ash microbeads, triterpenoid saponin and super absorbent resin are mixed and packaged separately as solid components, and modified polycarboxylic acid water reducer is packaged separately as liquid components. The solid components and liquid components are mixed when used to obtain the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage.

[0072] Example 4

[0073] An ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the modified polycarboxylic acid water-reducing agent is prepared by Preparation Example 2.

[0074] Example 5

[0075] An ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the modified polycarboxylic acid water reducer is prepared by Preparation Example 3.

[0076] Example 6

[0077] An ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the modified polycarboxylic acid water-reducing agent is prepared by Preparation Example 4.

[0078] Example 7

[0079] An ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the super absorbent resin is prepared by Preparation Example 5.

[0080] Comparative Example 1

[0081] An ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that an equal mass portion of polycarboxylate water reducer is used instead of a modified polycarboxylate water reducer.

[0082] Performance Test:

[0083] According to GB8076-2008 "Concrete Admixtures" standard, 0.18wt% of admixture was mixed with concrete and stirred evenly to prepare concrete samples. The concrete composition is shown in Table 1 below.

[0084] Table 1

[0085]

[0086] (1) Viscosity test: The viscosity of the concrete sample paste was measured by rheometer according to the standard of GB / T10274-2008 "Viscosity measurement method";

[0087] (2) Shrinkage test: The 28-day shrinkage of concrete samples was tested according to GB50204-2015 "Concrete Structure Engineering Quality Acceptance Code";

[0088] (3) Compressive strength test: According to GB50081-2019 "Test methods for physical and mechanical properties of concrete", the 3d and 28d compressive strength of concrete specimens were tested;

[0089] The concrete admixtures prepared in the embodiments and comparative examples were made into concrete specimens and tested according to the above test method. The test results are shown in Table 2.

[0090] Table 2

[0091]

[0092] It can be seen from the data in Table 2 that the concrete admixtures of Examples 1 to 3 can reduce the viscosity of concrete, improve the compressive strength of concrete and inhibit concrete shrinkage; in Example 4, due to the change in the molar ratio of 3-butenoic acid to cis-1,2-dihydroxymethylethylene, when the admixture is used in concrete, the viscosity of the concrete sample is slightly reduced, and the 3d and 28d compressive strengths are both reduced because hydroxypropyl methylcellulose and fumed silica cannot form a micro-crosslinked state with the modified polycarboxylic acid water-reducing agent well; in Example 5, due to the change in the molar ratio of propyltrimethoxysilane to compound A, the viscosity-reducing effect of the admixture is too obvious, resulting in a decrease in the 3d compressive strength of the concrete sample, but because the hydroxypropyl methylcellulose therein can form more crosslinks The mesh structure results in no significant change in the 28d compressive strength of the concrete sample; in Example 6, due to the change in the mass ratio of the modified polycarboxylate water-reducing agent precursor, fumed silica and hydroxypropyl methylcellulose, the viscosity reduction effect of the admixture is too obvious, resulting in a decrease in the 3d and 28d compressive strengths of the concrete sample; in Example 7, due to the change in the mass ratio of N,N-methylenebisacrylamide and compound B, the cross-linking density of the superabsorbent resin is too large, which is not conducive to the absorption of moisture, thereby reducing the internal curing capacity of the concrete, resulting in obvious shrinkage of the concrete test; in Comparative Example 1, due to the use of commercially available polycarboxylate water-reducing agent instead of modified polycarboxylate water-reducing agent, the viscosity reduction effect of the admixture is significantly reduced, and the 3d and 28d compressive strengths of the concrete sample are both reduced.

[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage, characterized in that: The composition comprises the following components by weight: 5-10 parts of nano powder, 20-35 parts of fly ash microspheres, 15-25 parts of modified polycarboxylic acid water reducer, 1-3 parts of air entraining agent and 5-15 parts of highly absorbent resin; The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps: (1) 3-Butenoic acid, cis-1,2-dihydroxymethylethylene and a solvent were mixed, concentrated sulfuric acid was added, the temperature was raised to 60-70°C and the mixture was stirred at a constant temperature for 8-10 hours, deionized water was added for extraction, the organic phase was collected, and the organic phase was concentrated under reduced pressure and subjected to column chromatography to obtain compound A; (2) Mix propyltrimethoxysilane, methanol and deionized water, heat to 80-100°C and stir at constant temperature for 1-1.5 hours, then add compound A and dilute nitric acid in step (1) and heat to 100-110°C and stir at constant temperature for 8-12 hours to obtain compound B; (3) Adding acrylic acid, compound B in step (2) and methacrylic acid polyethylene glycol ether to water, stirring at a constant temperature of 25-35° C. for 30-40 min, then adding an initiator, an oxidant and a reducing agent, heating to 65-75° C. and stirring at a constant temperature for 2-3 h, cooling to room temperature after the reaction is completed, and adjusting the pH of the system to 5-8 with a sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water-reducing agent precursor; (4) adding fumed silica and hydroxypropyl methylcellulose to the modified polycarboxylic acid water-reducing agent precursor in step (3), raising the temperature to 40-60° C. and stirring at a constant temperature for 8-10 hours to obtain a modified polycarboxylic acid water-reducing agent; In step (1), the molar ratio of 3-butenoic acid to cis-1,2-dihydroxymethylethylene is 1:(0.9-1); In step (2), the molar ratio of propyltrimethoxysilane to compound A is 1:(1-1.2); In step (4), the mass ratio of the modified polycarboxylate water-reducing agent precursor, fumed silica and hydroxypropyl methylcellulose is 1:(1-1.2):(0.4-0.8); The preparation method of the highly water-absorbent resin comprises the following steps: (I) maleic acid and thionyl chloride are mixed, the temperature is raised to 60-80°C and stirred at constant temperature for 0.5-1h, after the reaction is completed, the temperature is returned to room temperature, and the mixture is concentrated under reduced pressure to obtain compound C; (II) Compound C in step (I) is mixed with tetrahydrofuran, an acid binding agent is added thereto, and a chloroform solution of 1,2-propylenediamine is added dropwise at a rate of 5-10 mL / min. After the addition is complete, the mixture is stirred at room temperature for 2-4 hours. After the reaction is completed, the mixture is filtered, concentrated under reduced pressure, and subjected to column chromatography to obtain compound D; (III) N,N-methylenebisacrylamide, the compound D in step (II) and the initiator are dissolved in water, the temperature is raised to 65-75°C and stirred at a constant temperature for 20-24 hours, and after the reaction is completed, spray drying is performed to obtain a highly absorbent resin; In step (III), the mass of the N,N-methylenebisacrylamide is 0.07-0.09wt% of compound D.

2. The ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage according to claim 1, characterized in that: The nano powder is nano SiO2 and / or nano Al2O3.

3. The ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage according to claim 1, characterized in that: The air entraining agent is alkylbenzene sulfonate.

4. A method for preparing the ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing nano powder, fly ash micro beads, air entraining agent and super absorbent resin and packaging them separately as solid components, packaging modified polycarboxylic acid water reducer separately as liquid components, and mixing the solid components and the liquid components to obtain an ultra-high performance concrete admixture for reducing viscosity and inhibiting shrinkage.

Citation Information

Patent Citations

  • Viscosity reducing water-reducing agent

    CN114349384B

  • Viscosity reducing and water-reducing agents for high-strength concrete and their preparation methods

    CN116102691B

  • Low-shrinkage low-viscosity ultrahigh-strength concrete and preparation method thereof

    CN115403331A